Peran Calo Ilegal Dalam Proses Pengurusan Administrasi Di Kantor Samsat Kota Bengkulu - Muhamad Riski; Anita Marianata (CV. ITTC INDONESIA, 2024)
This study aims to analyze the factors that cause the prevalence of brokers in the administrative process at the Bengkulu City One-Stop Integrated Management System (SAMSAT) Office, as well as the impact on the community and prevention efforts that can be made. The method used is a quantitative approach with survey techniques through questionnaires distributed online to the public who use Samsat services. The results showed that the complexity of administrative procedures, uncertainty of waiting times, and lack of clear information were the main factors that led to the large number of brokers. The impact of brokers on the administrative process includes unfairness in access to services and decreased public trust in government institutions. Recommendations resulting from this research include improving information services, training for Samsat officers, and increasing transparency of administrative procedures. It is hoped that the results of this study can contribute to the improvement of public services and the reduction of touts in the Bengkulu City Samsat Office, as well as increase public trust in government agencies